Controlled Modulation of Folate Polyglutamyl Tail Length by Metabolic Engineering of Lactococcus lactis - Sybesma, Wilbert (American Society for Microbiology, 2003)
The dairy starter bacterium Lactococcus lactis is able to synthesize folate and accumulates >90% of the produced folate intracellularly, predominantly in the polyglutamyl form. Approximately 10% of the produced folate is released into the environment. Overexpression of folC in L. lactis led to an increase in the length of the polyglutamyl tail from the predominant 4, 5, and 6 glutamate residues in wild-type cells to a maximum of 12 glutamate residues in the folate synthetase overproducer and resulted in a complete retention of folate in the cells. Overexpression of folKE, encoding the bifunctional protein 2-amino-4-hydroxy-6-hydroxymethyldihydropteridine pyrophosphokinase and GTP-cyclohydrolase I, resulted in reduction of the average polyglutamyl tail length, leading to enhanced excretion of folate. By simultaneous overexpression of folKE and folC, encoding the enzyme folate synthetase or polyglutamyl folate synthetase, the average polyglutamyl tail length was increased, again resulting in normal wild-type distribution of folate. The production of bioavailable monoglutamyl folate and almost complete release of folate from the bacterium was achieved by expressing the gene for γ-glutamyl hydrolase from human or rat origin. These engineering studies clearly establish the role of the polyglutamyl tail length in intracellular retention of the folate produced. Also, the potential application of engineered food microbes producing folates with different tail lengths is discussed.